Determination of optimum parameters using grey relational analysis for multi-performance characteristics in CO2 laser joining of dissimilar materials - Tamrin, K. F.; Nukman, Y.; Sheikh, N.A.; Harizama, M.Z. (Elsevier Ltd., 2014)
This study concerns the employment of grey relational analysis to determine the optimized joint characteristics in CO2 laser lap joining of dissimilar materials classes. The joint characteristics, namely weld strength, weld width and kerf width are optimized as a function of laser power, its stand-off distance and the speed of welding. Due to a number of experimental constraints pertaining to joining polymer and glass-ceramic substrates, a full-factorial experiment is considered. Detailed images of the welded samples show the formation of crystallized glass leading to the failure of the joint. Thereafter, grey relational analysis (GRA) is employed to characterize the multiple quality characteristics of welded joint in terms of a relational grade. The set of the optimized processing parameters is determined based on the highest grade at 40 W laser power with a welding speed of 10 mm/s at a stand-off distance of 37 mm. Analysis of variance (ANOVA) is then carried out to ascertain the relative influence of process parameters on the joint characteristics. It was found that the weld speed has dominant effect on joint characteristics in comparison to stand-off distance at a fixed laser power.